2002
DOI: 10.4049/jimmunol.168.12.6253
|View full text |Cite
|
Sign up to set email alerts
|

The Immunodominant, Ld-Restricted T Cell Response to Hepatitis B Surface Antigen (HBsAg) Efficiently Suppresses T Cell Priming to Multiple Dd-, Kd-, and Kb-Restricted HBsAg Epitopes

Abstract: MHC-I-restricted CTL responses of H-2d (Ld+ or Ld−) and F1 H-2dxb mice to hepatitis B surface Ag (HBsAg) are primed by either DNA vaccines or HBsAg particles. The Dd/S201–209 and Kd/S199–208 epitopes are generated by processing endogenous HBsAg; the Kb/S208–215 epitope is generated by processing exogenous HBsAg; and the Ld/S28–39 epitope is generated by exogenous as well as endogenous processing of HBsAg. DNA vaccination primed high numbers of CTL specific for the Ld/S28–39 HBsAg epitope, low numbers of CTL sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
43
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 32 publications
4
43
0
Order By: Relevance
“…3C). The number of immunodominant CD8 T cells is apparently not important to suppress subdominant immune responses, confirming our previous reports in an HBV model (55,56).…”
Section: Priming Of E6-specific Cd8 T Cell Responses Critically Depensupporting
confidence: 78%
See 2 more Smart Citations
“…3C). The number of immunodominant CD8 T cells is apparently not important to suppress subdominant immune responses, confirming our previous reports in an HBV model (55,56).…”
Section: Priming Of E6-specific Cd8 T Cell Responses Critically Depensupporting
confidence: 78%
“…However, interference between responses to individual epitopes presented by the same or different MHC class I molecules is the well-established phenomenon of immunodominance that limits the repertoire diversity of CD8 T cell responses primed by such vaccines (18,19). We have shown that immunodominance hierarchies operate in CD8 T cell responses to different epitopes of the same Ag, between different Ags of the same virus, or between unrelated Ags (50,55,56,62,63). (56).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to consider, however, that the dominance of a particular epitope is not necessarily linked to the abundance of the epitope on the surface of the APC (26) and that the absence of an epitope or MHC molecule can lead to the conversion of a subdominant epitope to a dominant epitope (27,28). The results described here show that CD8 T cell immunodominance caused by competition between T cell clones for DCs can occur in the first few hours of a response.…”
Section: Discussionmentioning
confidence: 82%
“…Strikingly, under the latter circumstances, CD8 T cells respond to only a few immunodominant epitopes and neglect other potentially immunogenic peptides (cryptic epitopes). Restriction of CD8 T cell responses to a few selected epitopes has been termed immunodominance, a central and robust feature of immune responses (1)(2)(3)(4)(5)(6)(7)(8). At face value, immunodominance is counterintuitive.…”
mentioning
confidence: 99%